CCDE v3 practice labs : preparing for the Cisco Certified Design Expert Lab Exam - Duggan, Martin (Cisco Press, 2023)
CCDE Practice Labs is designed to guide and coach CCDE candidates through essential preparation for the newly-updated 8-hour, scenario-based Cisco CCDE Practical Exam V. 3.0. Authored by an expert CCDE who contributed to the latest exam update, it presents three highly-realistic scenario-based lab exams. All three are carefully designed to match the complexity and format of the real exam, and are supported with detailed debriefs explaining why the correct answers are right and the "distractors" are wrong. CCDE Martin James Duggan draws on his deep experience designing global Cisco networks, and mentoring colleagues at one of the world’s largest networking organizations. Duggan begins by presenting an insider’s overview of the revised exam blueprint. Throughout, he focuses on “why,” not just “how”helping you develop the right mindset to succeed, thoroughly evaluate your readiness, and address any gaps in the practical knowledge you’ll need to pass. With the new update, CCDE is a more valuable and prestigious credential than everbut high-quality cost-effective lab training has been scarce. CCDE Practice Labs fills that gap, helping you gain the practical expertise you need to take your CCDE Practical Exam V. 3.0 with confidence.